Virtual reality in visual rehabilitation - M. V. Zueva; V. I. Kotelin; N. V. Neroeva; A. N. Zhuravleva; I. V. Tsapenko (Российский офтальмологический журнал)
The review discusses the current state of affairs and prospects for the use of virtual reality (VR) technologies in visual rehabilitation strategies based on neuroplasticity activation. Vision training in VR has a number of advantages compared to traditional rehabilitation activities. Play-based VR exercises, practices in a safe and controlled environment, attract the users and encourage them to actively participate in therapy and comply with the treatment plan. VR systems have options that enable the creation of individual treatment programs tailored to the specific needs and abilities of each patient. VR systems are only beginning to be used in the rehabilitation of visually impaired but on the whole show promising results already. Yet, more careful evaluation of the results and additional research are required to overcome the existing limitations of the approach, such as a small size of the sample and lack of control groups. Objective diagnostic methods are needed to create a solid and high-quality evidence base. It seems promising to expand the potentials of VR technologies for visual rehabilitation of diverse retinal pathology patients by combining visual training in the virtual world with rhythmic photostimulation using optimal parameters of optical signals.